A comparison of the performance of the Braden Q and the Glamorgan paediatric pressure ulcer risk assessment scales in general and intensive care paediatric and neonatal units. Issue 2 (May 2016) - Willock, Jane; Habiballah, Laila; Long, Deborah; Palmer, Kelli; Anthony, Denis
Abstract: Aims: To compare the predictive ability of two risk assessment scales used in children. Background: There are several risk assessment scales (RASs) employed in paediatric settings but most have been modified from adult scales such as the Braden Q whereas the Glamorgan was an example of a scale designed for children. Methods: Using incidence data from 513 paediatric hospital admissions, receiver operating characteristic (ROC) was employed to compare the two scales. The area under the curve (AUC) was the outcome of interest. Results: The two scales were similar in this population in terms of area under the curve. Neonatal and paediatric intensive care were similar in terms of AUC for both scales but in general paediatric wards the Braden Q may be superior in predicting risk. Conclusion: Either scale could be used if the predictive ability was the outcome of interest. The scales appear to work well with neonatal, paediatric intensive care and general children's wards. However the Glamorgan scale is probably preferred by childrens' nurses as it is easy to use and designed for use in children. There is some suggestion that while the two scales are similar in intensive care, for general paediatrics the Braden Q may be the better scale. Highlights: There are several risk paediatric pressure ulcer risk assessment scales. The Glamorgan and Braden Q scales appear to work well with neonatal, paediatric intensive care and general children's wards. There is some evidence Braden Q may be better in general paediatrics.